A Phenomenological Study on Entrepreneurial Identity of Female Entrepreneurs in South Africa - Semukele Hellen Mlotshwa; McEdward Murimbika (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Objective: To understand the entrepreneurial identity, through the lived experience of female entrepreneurs who are familiar with the phenomenon. This objective was premised on understanding that entrepreneurial identity is a product of context which shapes the social-cultural norms and environment within which individuals, operate and construct their identity. This is captured in entrepreneurship scholarship where the discipline is still struggling to build a reliable definition of female entrepreneurship applicable to both developed and developing countries and its effect on their respective economies. Research Design & Methods: This study used a qualitative research design that followed a phenomenological approach with thirty five female entrepreneurs, utilising semi structured in depth individual meetings. Findings: Female entrepreneurs build, balance, and manage a wide range of entrepreneurial ventures of varying sizes across sectors while maintain both role and social identities. Female entrepreneurs also express strong views on earning returns and income to not only grow their business but support their employees, communities, themselves, and their families. Implications & Recommendations: This study generated five themes that should be researched quantitatively to determine further understanding of entrepreneurship and developing other entrepreneurs in developing countries. Contribution & Value Added: The study contributes to the existing body of knowledge on entrepreneurship in entrepreneurial identity, by exploring the female entrepreneur as both a role and identity. It examines this through the perspective of role identity and learn how female entrepreneurs consider their role as an entrepreneur.